Integration of forming operations on hybrid additive manufacturing systems based on fusion welding - Pragana, João (2020)
This paper is focused on the integration of metal forming operations in hybrid systems that combine additive manufacturing (AM) by gas metal wire arc and subtractive manufacturing by machining. The investigation is carried out in AISI 316L stainless steel wire and draws from tensile testing to incremental sheet forming of truncated conical shapes. Commercial sheets from the same material are utilized for comparison purposes. Thickness measurements, digital image correlation (DIC), circle grid analysis (CGA) and microstructural and scanning electron microscopy (SEM) observations are carried out to understand how different is the mechanical behaviour of the deposited metal from that of commercial metal sheets and how significant is the influence of the deposited metal microstructure on its overall formability. Results confirm that integration of metal forming operations in hybrid AM routes is feasible despite the formability of deposited metal being smaller than that of the commercial metal sheets due to the strong anisotropy induced by the dendritic based microstructure of the deposited metal. Incremental forming of two deposited parts also allows concluding that integration of metal forming operations in hybrid AM systems is a step towards green and sustainable manufacturing by extending their field of applicability to the fabrication of complex ready-to-use parts requiring combination of different processes.